Contribution of Riba-Free Banking System on Rural Development in Bangladesh: A Projection for Vision-21 (Global Journal of Management and Business Research, 2015)
Ribe-Free Banking System (RFBS) is the most economic domain in the micro-finance area for the rural development as well as the economic development of Bangladesh. Rural development Scheme (RDS), the specialized form of Banking operations of Islami Bank Bangladesh Limited (IBBL), is offered for those people who live below the poverty and absolute poverty level in Bangladesh. The basic aim of this study is to examine the impact of RDS of IBBL on National GDP through rural development. The RDS of IBBL is the project sample of this study. The annual time-series data from FY 2002-2003 to FY 2013-2014 are used in this study for justifying the rural development through identifying the impact on GDP. This study has found that deposit and investment of RDS of IBBL have strong and significant impact on national GDP. The findings of the study will be helpful for the economic policy makers of the concerned authority of Bangladesh in reshaping the economic activities aiming at achieving the goal stated for the Vision-21, the golden jubilee of the independence of Bangladesh.
Keywords: Riba-Free Banking; rural development; RDS; vision-21; granger causality test